Proclaiming and cultivating childlikeness': a subversive thread in Christian anthropology - Wrigley-Carr, Robyn (International journal of children's spirituality, 2018)
If contemporary public discourse struggles with truncated notions of what it means to be human, nowhere is this more obvious than in our discussion and treatment of children. By and large, in our public discourse, we treat children as little adults' - as consumers, objects of beauty and fashion, career aspirants and sometimes even as sexual beings. By contrast, Jesus put children - as children - at the centre of his project in proclaiming the kingdom of God. He preserved a special place for children in his ministry, and in all three synoptics, he called his followers to childlikeness'. This paper examines a subversive thread in historic theological anthropology. The nature of childlikeness' is explored and possible ways to cultivate childlikeness for adults are discussed. The notion of childlikeness has been rediscovered in recent times by the Child Theology Movement', but, in this paper, I wish to examine three linked authors who wrote on childlikeness' in the 19th and 20th centuries, predating the Child Theology Movement by some decades: George MacDonald, Baron Friedrich von Hügel and Gwendolen Greene.